The effects of self-efficacy, social support, and mental toughness on tennis umpires’ professional identity: a study based on a latent variable mediation model - Zhou, Xielin; Luo, Lan; Liu, Quandong; Li, Bo; Wen, Linfeng (Frontiers in Psychology, 2025)
PurposeTo explore the relationship between self-efficacy and professional identity among tennis umpires, and to explore the mediating role of mental toughness and social support in this process.MethodsThe Self-Efficacy Scale (GSES), Vocational Identity Scale (VISA), Mental Toughness Scale (CD-RISC10), and Social Support Scale (SSRS) were used to survey 399 tennis umpires in S Province from November 12, 2024, to November 19, 2024.Results(1) Correlation analysis showed that self-efficacy and occupational identity showed a significant positive correlation (r = 0.544, p < 0.01), self-efficacy and social support showed a significant positive correlation (r = 0.444, p < 0.01), self-efficacy and mental toughness showed a significant positive correlation (r = 0.432, p < 0.01), social support and mental toughness showed a significant positive correlation (r = 0.432, p < 0.01), and social support and mental toughness showed a significant positive correlation (r = 0.609, p < 0.01) (0.432, p < 0.01), social support showed a significant positive correlation with occupational identity (r = 0.609, p < 0.01), and mental toughness showed a significant positive correlation with occupational identity (r = 0.504, p < 0.01). (2) The results of path analysis showed that self-efficacy significantly and positively affected mental toughness (β = 0.165, p < 0.01) and social support (β = 0.593, p < 0.01); mental toughness significantly and positively affected social support (β = 0.437, p < 0.01); and social support significantly and positively affected occupational identity (β = 0.867, p < 0.01). (3) The results of the mediating effect showed that mental toughness partially mediated between self-efficacy and occupational identity, with an effect size of 0.067 and a 95% confidence interval of [0.006, 0.126]; and social support and mental toughness chained the mediating effect between self-efficacy and occupational identity. The effect size was 0.120 with a 95% confidence interval of [0.065, 0.190].Conclusion(1) Tennis umpires’ self-efficacy, social support, and mental toughness showed a two-by-two positive correlation with professional identity. (2) Mental toughness plays a simple mediating role between self-efficacy and professional identity, and social support and mental toughness mediate between the two.